(untitled) (Nexo Revista Científica, 2025)
The aim of this study was to evaluate the antioxidant activity and the sensory preference of commercial goat milk cheeses. Different brands (N=6) of commercial goat milk (i.e., white, fresh and Feta-type cheeses) were evaluated for their antioxidant activity using the DPPH method. Sensory evaluation was conducted to determine the preference of the cheeses. Overall, the antioxidant activity of cheeses ranged from 158 to 233 μM of Trolox/mL. Particularly, it was observed that the Feta-type cheeses exhibited the lowest antioxidant activities, whereas white fresh-cheeses were those with highest antioxidant activities. The sensory preference of the cheeses was variable, being the most preferred a sample representative of each cheese type. This study demonstrates that these commercial goat milk cheeses are sources of potential antioxidant compounds.